Climate risks and vulnerabilities in African agrifood systems - Yade, Sambane; Dia, Khadim; Grace, Delia (AKADEMIYA2063, 2024)
In an era when the impacts of climate change are becoming increasingly pronounced, understanding and mitigating climate risk is paramount, especially for regions highly vulnerable to environmental change. Africa, with its rich biodiversity and varied climates, stands on the front line, facing unique challenges posed by climate change and climate variability. The continent’s susceptibility around climate change is not just a matter of environmental concern but a multifaceted issue affecting socioeconomic development, agricultural sustainability, and the overall well-being of its inhabitants. The imperative to assess, comprehend, and adapt to these risks is more critical now than ever, necessitating a detailed analysis of various climate-related parameters and their long-term implications.